2022
DOI: 10.1039/d2qi01224c
|View full text |Cite
|
Sign up to set email alerts
|

Antimony -doped indium-based halide single crystals enabling white-light emission

Abstract: Metal ion doping strategy is employed to achieve white light emission in metal halides materials, while it is still challenging to explore lead-free metal halides. Here we report a series...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…We focus on low-dimensional chiral indium-and antimony-based compounds, which have been extensively reported with high PLQYs in achiral compounds. [9] We first synthesize chiral indium chlorides templated by chiral organic cations including (R)-(+)-βmethylphenethylammonium (R-MPA + ) and (R)-(À )-1cyclohexylethylammonium (R-CHEA + ), affording (R-MPA) 2 InCl 5 and (R-CHEA) 4 In 2 Cl 10 . These two compounds display essentially no observable PL at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on low-dimensional chiral indium-and antimony-based compounds, which have been extensively reported with high PLQYs in achiral compounds. [9] We first synthesize chiral indium chlorides templated by chiral organic cations including (R)-(+)-βmethylphenethylammonium (R-MPA + ) and (R)-(À )-1cyclohexylethylammonium (R-CHEA + ), affording (R-MPA) 2 InCl 5 and (R-CHEA) 4 In 2 Cl 10 . These two compounds display essentially no observable PL at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast production process from free exciton to self-trapped exciton is a nonadiabatic transition of the femtosecond magnitude (<210 fs). The excited-state 5s 2 of Sb 3+ split into one singlet-state 1 P 1 and triplet-state 3 P n ( n = 0, 1, 2), and the 1 S 0 → 1 P 1 and the 1 S 0 → 3 P 1 transition is allowed and partially allowed due to spin–orbital coupling. , When doping ns 2 -based metal cation Sb 3+ , electrons in the ground state are excited to the excited states and then transferred to 3 P 1 states upon photoexcitation at 353 nm. Due to the “intermediate state” Sb 3+ , energy barriers are decreased and the nonradiative recombination process is suppressed, resulting in promoting the process from excited states to 3 P 1 states.…”
Section: Resultsmentioning
confidence: 99%
“…In general, In-based OIMHs can easily crystallize with water or organic solvent molecules, which causes the structures to collapse upon losing their solvent molecules at lower temperatures. 14,46 In comparison, (DETA)InCl 6 has the advantage of good thermal stability. Metal doping strategies are usually effective ways to change the emission band and improve the quantum efficiency.…”
Section: Crystal Structures and Supramolecular Interactionsmentioning
confidence: 99%
“…Specifically, indium-based compounds have low toxicity and better chemical stability in air, hence, they are regarded as a potential substitute for Pb 2+ -based compounds. [12][13][14] Recently, Yue et al 15 ) + ] indium-based hybrid halides, which exhibited strong broadband orange luminescence with a PLQY of about 35%. 16 Subsequently, Yuan et al 17 reported 0D In-based OIMH (C 10 H 22 N 2 ) 2 In 2 Br 10 with high-efficiency intrinsic emission and a PLQY of up to 70%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation